Natural law in English Renaissance literature / R.S. White. - White, R. S., 1948- (Cambridge University Press, 1996)
Natural law, whether grounded in human reason or divine edict, encourages men to follow virtue and shun vice. The concept dominated Renaissance thought, where its literary equivalent, poetic justice, underpinned much of the period's creative writing. R. S. White's study examines a wide range of Renaissance texts, by More, Spenser, Sidney, Shakespeare and Milton, in the light of these developing ideas of Natural Law. It shows how writers as radically different as Aquinas and Hobbes formulated versions of Natural Law which served to maintain socially established hierarchies. For Aquinas, Natural Law always resided in the individual's conscience, whereas Hobbes thought individuals had limited access to virtue and therefore needed to be coerced into doing good by the state. White shows how the very flexibility and antiquity of Natural Law enabled its appropriation and application by thinkers of all political persuasions in a debate that raged throughout the Renaissance and which continues in our own time.